The influence of foreign direct investments on Montenegro payment balance - Ana Gardasevic (UTMS Journal of Economics, 2013)
In this work, with help of econometric analysis we will answer the question to which extent up to date foreign direct investments influenced Montenegro current account. Regression analysis brings to conclusion that if foreign direct investments should increase for 1%, current account deficit will increase for 0.00024% after the first quarter and 0.000227% after the second quarter. More significant effects from the direct foreign investments on Montenegrin payment balance could be seen in some period in future, if it would concentrate on new "more quality" foreign direct investments that would be export oriented. Knowing that foreign direct investments were the main source of funding current account deficit in the previous period, and that absorption possibilities for the inflow of foreign direct investments still exist, it should be continued with attracting the same mentioned, because it can help in the change of production and export structure, because with current level of domestic savings and outside debt it is unimaginable.
Keywords: F3; 330; foreign direct investments; greenfield investments; payment balance; regression analysis